Pregnancy with active Takayasu's arteritis: A medical challenge - Manu Goyal; Neha Agrawal; Pratibha Singh; Shafaq Bhandari (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2020)
Takayasu arteritis is a large vessel vasculitis, and very rare in occurrence with pregnancy. It usually complicates the latter half of pregnancy and causes hypertension, organ dysfunction, fetal growth restriction. Its management during pregnancy is a medical challenge.  Here we present a case of 25-year old primigravida presented to us at 30 weeks with Takayasu arteritis and its successful management with good fetomaternal outcome.